Perancangan Sistem Absensi Online Pegawai Berbasis Web (Studi Kasus Pemko Sibolga) - Sitorus, Putri Ayu; Arpan; Muhammad Amin (Jurnal Mahajana Informasi, 2024)
The employee attendance process is an important aspect in human resource management in government agencies, including the Sibolga City Government. The manual attendance system currently used in the Sibolga City Government has several weaknesses, such as the possibility of data input errors, slow attendance recapitulation process, and difficulty in monitoring attendance in real time. To overcome this problem, this study developed a web-based online attendance system that can improve the efficiency and accuracy of employee attendance recording. The methods used in this study include analysis of the current system, design of a new system, implementation, and software testing using the Black Box Testing method. This system was developed using web-based software with the PHP programming language and MySQL database managed through the XAMPP platform. This online attendance system allows employees to take attendance digitally through devices connected to the internet, while officers can easily manage and monitor attendance data. The results of the study show that the developed online attendance system can run according to its function and meet the needs of the Sibolga City Government. This system is able to reduce data recording errors, speed up the recapitulation process, and provide convenience in monitoring employee attendance. Thus, it is hoped that this online attendance system can increase the effectiveness and efficiency of employee attendance management at the Sibolga City Government.